Short communication: Evaluation of charged membrane filters and buffers for concentration and recovery of infectious salmon anaemia virus in seawater - Weli, Simon Chioma; Tartor, Haitham; Spilsberg, Bjørn; Dale, Ole Bendik; Lillehaug, Atle (PloS one, 2021)
Infectious salmon anaemia virus (ISAV) is the cause of an important waterborne disease of farmed Atlantic salmon. Detection of virus in water samples may constitute an alternative method to sacrificing fish for surveillance of fish populations for the presence of ISA-virus. We aimed to evaluate different membrane filters and buffers for concentration and recovery of ISAV in seawater, prior to molecular detection. One litre each of artificial and natural seawater was spiked with ISAV, followed by concentration with different filters and subsequent elution with different buffers. The negatively charged MF hydrophilic membrane filter, combined with NucliSENS ® lysis buffer, presented the highest ISAV recovery percentages with 12.5 ± 1.3% by RT-qPCR and 31.7 ± 10.7% by RT-ddPCR. For the positively charged 1 MDS Zeta Plus ® Virosorb ® membrane filter, combined with NucliSENS ® lysis buffer, the ISAV recovery percentages were 3.4 ± 0.1% by RT-qPCR and 10.8 ± 14.2% by RT-ddPCR. The limits of quantification (LOQ) were estimated to be 2.2 x 10 3 ISAV copies/L of natural seawater for both RT-qPCR and RT-ddPCR. The ISAV concentration method was more efficient in natural seawater.